2011
DOI: 10.1099/mic.0.045054-0
|View full text |Cite|
|
Sign up to set email alerts
|

Glutathione biosynthesis in the yeast pathogens Candida glabrata and Candida albicans: essential in C. glabrata, and essential for virulence in C. albicans

Abstract: Redox pathways play a key role in pathogenesis. Glutathione, a central molecule in redox homeostasis in yeasts, is an essential metabolite, but its requirements can be met either from endogenous biosynthesis or from the extracellular milieu. In this report we have examined the importance of glutathione biosynthesis in two major human opportunistic fungal pathogens, Candida albicans and Candida glabrata. As the genome sequence of C. glabrata had suggested the absence of glutathione transporters, we initially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…3E). Cystathionine is also present at low levels in blood plasma (3). Not surprisingly, we observed that cystathionine could also be used efficiently as a sulfur source in this yeast.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…3E). Cystathionine is also present at low levels in blood plasma (3). Not surprisingly, we observed that cystathionine could also be used efficiently as a sulfur source in this yeast.…”
Section: Discussionmentioning
confidence: 58%
“…Cellular Localization of HA-tagged CgCYN1-For the localization studies Cgmet15⌬CYN1⌬ was transformed with the 3 The abbreviations used are: ARC, American Radiolabeled Chemicals; PGK, phosphoglycerate kinase; TEF, translation elongation factor. HA-tagged CgCYN1, and the transformants were used for the indirect immunofluorescence as described earlier (16).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations